2020
DOI: 10.1016/j.jad.2020.05.054
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of modified, group-based CBT for dementia worry among Chinese elders

Abstract: Dementias are highly prevalent among Chinese elders. This study examined the effectiveness of a modified group cognitive behavioral therapy (CBT) on dementia worry among Chinese older adults. Methods: Eighty-two older adults recruited from four elder group homes were randomly assigned to either intervention or control group. The intervention group (n= 44) received eight weekly 60-minute face-to-face CBT, while the control group (n=38) received treatment-as-usual.Results: Outcomes indicated that the modified gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Assuming there is a causal relationship between cognitive health worries and psychological wellbeing, finding ways of reducing these cognitive health worries will benefit wellbeing in this population. For example, a modified cognitive behavioural therapy (CBT) programme has been used successfully to reduce dementia worry in a sample of older adults ( An et al, 2020 ), but it did not include measures of wellbeing. A potential alternative could be a cognitive training programme; hypothetically, improving cognitive functioning could lessen cognitive health worries, if the participant believes that the cognitive training is working.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming there is a causal relationship between cognitive health worries and psychological wellbeing, finding ways of reducing these cognitive health worries will benefit wellbeing in this population. For example, a modified cognitive behavioural therapy (CBT) programme has been used successfully to reduce dementia worry in a sample of older adults ( An et al, 2020 ), but it did not include measures of wellbeing. A potential alternative could be a cognitive training programme; hypothetically, improving cognitive functioning could lessen cognitive health worries, if the participant believes that the cognitive training is working.…”
Section: Discussionmentioning
confidence: 99%
“…Most dementia awareness programs adopted an educational approach without a coordinated linkage to counseling or psychosocial services that are deemed necessary for dementia worry (An et al, 2020). One psychosocial intervention study has shown a promising effect in reducing dementia worry among residents living in elder care facilities in Shanghai, China (An et al, 2020). As family conflict is an associate of dementia worry found in this study, psychosocial interventions to reduce dementia worry can include components to address family conflict for older Chinese Americans.…”
Section: Implications For Practice and Policymentioning
confidence: 86%
“…Finally, multiple intervention approaches including psychosocial education and counseling should be made available to help address dementia worry. Most dementia awareness programs adopted an educational approach without a coordinated linkage to counseling or psychosocial services that are deemed necessary for dementia worry (An et al, 2020). One psychosocial intervention study has shown a promising effect in reducing dementia worry among residents living in elder care facilities in Shanghai, China (An et al, 2020).…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Getting dementia is a tremendous stressor in an ageing society, especially in China, where the ageing population is growing fast and the population of people over the age of 60 is projected to reach 28% in the near future. Since many Chinese adults are influenced by the notion of ‘filial piety expectations’ and ‘elder respect’ in Chinese culture, they hold the idea that older people are usually wiser, and thus older adults may be more fearful towards getting dementia, potentially suffering negative health outcomes because of it (An et al, 2020; North & Fiske, 2015). One way to reduce this consequence of the fear of dementia may be through effective health education for the general public and older adults, so as to reduce negative stereotypes and fears towards ageing and dementia.…”
Section: Discussionmentioning
confidence: 99%